Vaccination of pigs reduces Torque teno sus virus viremia during natural infection. Issue 30 (9th July 2015) - Jiménez-Melsió, Alexandra; Rodriguez, Fernando; Darji, Ayub; Segalés, Joaquim; Cornelissen-Keijsers, Vivian; van den Born, Erwin; Kekarainen, Tuija
Highlights: Vaccination against TTSuVk2a resulted in a delay and lower viral load in immunized pigs. Vaccinated pigs were seroconverted against TTSuVk2a proteins. A combination of DNA and protein immunization can control TTSuVk2a viremia. Abstract: Anelloviruses are a group of single-stranded circular DNA viruses infecting several vertebrate species. Four species have been found to infect swine, namely Torque teno sus virus (TTSuV) 1a and 1b (TTSuV1a, TTSuV1b; genus Iotatorquevirus ), TTSuVk2a and TTSuVk2b (genus Kappatorquevirus ). TTSuV infection in pigs is distributed worldwide, and is characterized by a persistent viremia. However, the real impact, if any, on the pig health is still under debate. In the present study, the impact of pig immunization on TTSuVk2a loads was evaluated. For this, three-week old conventional pigs were primed with DNA vaccines encoding the ORF2 gene and the ORF1-A, ORF1-B, and ORF1-C splicing variants and boosted with purified ORF1-A and ORF2 Escherichia coli proteins, while another group served as unvaccinated control animals, and the viral load dynamics during natural infection was observed. Immunization led to delayed onset of TTSuVk2a infection and at the end of the study when the animals were 15 weeks of age, a number of animals in the immunized group had cleared the TTSuVk2a viremia, which was not the case in the control group. This study demonstrated for the first time that TTSuV viremia can be controlled by a combined DNA and protein immunization, especially apparent two weeks after the first DNA immunization before seroconversion was observed. Further studies are needed to understand the mechanisms behind this and its impact for pig producers.